Determining wireless local area network (WLAN) vulnerabilities on academic network - Azzali, Fazli; Ahmad, Amran; Daud, Ali Yusny (2009)
The advancement and proliferation of wireless local area network nowadays have driven for an alarm on the whole network operation.The concern applies to both business and academic computer network environments.This paper describes our research and experiences in performing network vulnerabilities analysis in academic local area network.The research uses network vulnerability analysis methodology to perform vulnerability analysis on Academic and Administration building. From the analysis, the overall network security level can be determined.Remedies and solution to counter any vulnerability can also be prescribed and this will reduce network vulnerability threat to academic local area network.